Islamic Scientific Research: Its Importance in Serving Society and Mechanisms for its Integration - Klaina, Mekki (Al-Fadlan: Journal of Islamic Education and Teaching, 2024)
This research explores the effective integration of scientific, research into community service, emphasizing how Islamic scholarship can significantly enhance societal well-being. The study combines Islamic teachings with contemporary sciences such as psychology, technology, and environmental studies to address urgent societal issues. Utilizing a comprehensive mixed-methods approach, it assesses the impact of interdisciplinary research in real-world applications, demonstrating the pivotal role of combining traditional knowledge with modern scientific inquiry. Key findings highlight the importance of collaboration across different disciplines and the enhancement of community services through innovative research strategies. The study further argues for the advancement of knowledge by building on previous scholarly work, advocating for a dynamic rather than static approach to academic research. It underscores the necessity of ongoing academic dialogue and practical application to foster a society that values both tradition and innovation. Recommendations call for increased support for interdisciplinary research initiatives and the establishment of more platforms for collaboration between Islamic scholars and scientists from various fields to foster a holistic approach to addressing contemporary challenges.